Maternal sepsis caused by Listeria monocytogenes with a fatal fetal outcome. Issue 10 (3rd October 2022) - Dunphy, Louise; Polkampali, Mamatha; Simmons, William; Fowler, Grace
Abstract : Improving maternal and child health is a global priority. Although infection with Listeria monocytogenes (LM), a small facultative anaerobic, gram-positive motile bacillus is rare, when it infects the maternal-fetoplacental unit, it can result in adverse fetal sequelae such as chorioamnionitis, preterm labour, neonatal sepsis, meningitis and neonatal death. Pregnancy-associated listeriosis may present with a plethora of diverse, non-specific symptoms such as fever, influenza-like or gastrointestinal symptoms, premature contractions and preterm labour. It has a predilection for the second and third trimester of pregnancy, occurring sporadically or as part of an outbreak, most of which have involved unpasteurised dairy products, long shelf life products, contaminated ready-to-eat food, deli meats and soft cheeses. Strains belonging to the clonal complexes 1, 4 and 6 are hypervigilant and are commonly associated with maternal-neonatal infections. Maternal listeriosis occurs as a direct consequence of LM-specific placental tropism, which is mediated by the conjugated action of internalin A and internalin B at the placental barrier. The diagnosis is established from placental culture. Penicillin, ampicillin and amoxicillin are the antimicrobials of choice. It has a high fetal morbidity of up to 30%. The authors present the case of a multiparous woman in her early 20s presenting with sepsis and preterm premature rupture of her membranes at 21 weeks gestation. A live baby was delivered spontaneously and died shortly after birth. Placental cultures and postmortem examination were consistent with the diagnosis of disseminated Listeria infection. Due to the increased susceptibility of pregnant women for LM, a high index of clinical suspicion is required to establish the diagnosis and initiate appropriate antimicrobial therapy to reduce adverse fetal outcomes.